Synergistic Ultramicropore and Hierarchical Pore Engineering in Heteroatom-Doped Carbon for High-Performance Zinc-Ion Capacitors - Zhang, Jiale; Zhang, Ruifang; Du, Yangbo; Zhang, Shuaihua; Gao, Runze; Huang, Xuanqi; Yang, Qi; Kong, Debin; Xiao, Zhichang (Nano-Micro Letters, 2026)
Carbonaceous zinc-ion capacitors (ZICs) offer inherent advantages for energy storage, yet the role of pore structures in enabling high zinc-ion capacitance remains underexplored. Herein, a dual-molten-salt regulation strategy is employed to derive N/O/S-doped porous carbon nanomaterials, achieving a high specific surface area (SSA) of 2523 m2 g−1 with ultramicropores (< 0.86 nm) contributing 30.6% of the total SSA. Structural analyses reveal that increasing molten FeCl3 content yields materials with comparable heteroatom contents and defect structures, but a progressive shift from ultramicropores to mesopores. Crucially, the individual contributions of the pore structure are decoupled by both in situ characterizations and theoretical simulations: The ultramicropores facilitate the desolvation of [Zn(H2O)6]2+ (ultramicropore effect), while the hierarchical pores ensure rapid ion transport (hierarchical pore effect). The optimized HHPC-2 delivers a high specific capacitance of 222.6 F g−1 at 1 A g−1 and an energy density of 120.0 Wh kg−1 in ZICs. Intriguingly, its outstanding oxygen reduction reaction catalytic activity enables self-charging upon air exposure after a full discharge, achieving a self-charging rate of 15 mAh g−1 h−1 and recovering 80% of the externally charged capacity in subsequent discharge cycles. This positions the device as highly promising for practical deployment in regions with intermittent grid power supplies. Highlights: 1 A series of N/O/S-doped porous carbons are synthesized through a dual-molten-salt regulation strategy with controllable ultramicropore and mesopore structures. 2 The distinct functions of ultramicropores and hierarchical pores are delineated experimentally and theoretically, demonstrating that ultramicropores are crucial for facilitating the desolvation of [Zn(H2O)6]2+, while the hierarchical network ensures rapid ion transport. 3 The optimized cathode delivers a high specific capacitance (336.9 F g−1), outstanding energy density (120.0 Wh kg−1) and excellent air self-charging capability.